2007
DOI: 10.1136/bjsm.2007.036210
|View full text |Cite
|
Sign up to set email alerts
|

Match activity and physiological responses during a junior female singles tennis tournament

Abstract: Objective: To assess physiological load in conjunction with individual patterns of match-play activity in junior female tennis players during actual singles tennis competition. Methods: Eight elite junior female tennis players (n = 8; mean (SD) age, 17.3 (1.9) years) took part in a 2 day invitational tournament. Activity pattern analysis was performed during competitive matches. Heart rate and blood lactate concentrations were measured during selected changeovers breaks in play. Results: The activity profile o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
65
2
15

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(98 citation statements)
references
References 28 publications
(44 reference statements)
8
65
2
15
Order By: Relevance
“…USA) was used for the analysis of the matches, and the analysis of all of the matches was performed by the same experienced researcher. A match protocol developed by Smekal et al (2001), which had been shown to be reliable (Fernandez et al, 2007, 2008; Mendez-Villanueva et al, 2007, 2010) was used to monitor and record the duration of each game and each rally, the duration of the rest intervals between games and changeover breaks, as well as the number of shots per rally. On the basis of these data, the following variables were calculated for each game: 1- the duration of the rallies in seconds (DR); 2 - the rest time in seconds, not including changes of ends (RT); 3 - the work-torest ratio, not including changes of ends (W:R); 4 - effective playing time (EPT; expressed as a percentage of the total time when the ball was in play during a game); and 5 - strokes per rally (SPR; strokes·min-1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…USA) was used for the analysis of the matches, and the analysis of all of the matches was performed by the same experienced researcher. A match protocol developed by Smekal et al (2001), which had been shown to be reliable (Fernandez et al, 2007, 2008; Mendez-Villanueva et al, 2007, 2010) was used to monitor and record the duration of each game and each rally, the duration of the rest intervals between games and changeover breaks, as well as the number of shots per rally. On the basis of these data, the following variables were calculated for each game: 1- the duration of the rallies in seconds (DR); 2 - the rest time in seconds, not including changes of ends (RT); 3 - the work-torest ratio, not including changes of ends (W:R); 4 - effective playing time (EPT; expressed as a percentage of the total time when the ball was in play during a game); and 5 - strokes per rally (SPR; strokes·min-1).…”
Section: Methodsmentioning
confidence: 99%
“…Further studies have investigated performance responses in matches, using methods such as time-motion analysis (Gomes et al, 2011; Vickery et al, 2014) and activity profiles (Fernandez et al, 2007, 2008, 2009b) in players of different levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rallies duration and the shots per rally were encoded as has been carried out in other studies. [17][18][19] From these data, the following variables were calculated for the six matches analysed:…”
Section: Match Analysesmentioning
confidence: 99%
“…Al igual que en otros deportes de raqueta, en el pádel, la actividad física implica esfuerzos de alta intensidad como sprints, saltos y golpeos agresivos de la pelota, intercalados con periodos de baja o nula intensidad (Martin, 2013). En las investigaciones precedentes se han analizado las características antropométricas, fisiológicas y de juego en otros deportes de raqueta como el tenis (Christmass et al, 1998;Ferrauti et al, 2001;Méndez-Villanueva et al, 2007;Méndez-Villanueva et al, 2010;Kovacs, 2007;Girard y Millet, 2009;Fernández-Fernández et al, 2007;Fernández-Fernández et al, 2008;Fernández-Fernández et al, 2009), el badminton (Faude et al, 2007;Cabello y González-Badillo, 2003;Torres et al, 2004), el squash (Wells et al, 2004;Vuckovic et al, 2004;Girard et al, 2007) o el tenis de mesa (Zagatto et al, 2010), dichas investigaciones han contribuido al desarrollo del juego y a concretar las necesidades específicas de cada uno de ellos.…”
Section: Introductionunclassified